An oral absorbent, AST-120, restores vascular growth and blood flow in ischemic muscles in diabetic mice via modulation of macrophage transition. (June 2021) - Huang, Hsin-Lei; Kuo, Chin-Sung; Chang, Ting-Yung; Chou, Ruey-Hsing; Chen, I-Chun; Yang, Fu-Chen; Chen, Nien-Jung; Lin, Shing-Jong; Wu, Chih-Cheng; Huang, Po-Hsun
Abstract: Background Diabetes has a pronounced effect on the peripheral vasculature. The accumulation of advanced glycation end products (AGEs) is regarded as the crucial mechanism responsible for vascular damage in diabetes, but it is not easy to be avoided from food. In this study, we aimed to investigate the effects of an oral absorbent, AST-120, on the accumulation of AGEs and changes in blood flow recovery in diabetic mice. Methods The mice were divided into four groups, wild-type (WT) mice without treatment, WT mice treated with 5% AST-120 mixed into pulverized chow, streptozotocin-induced diabetes mellitus (DM) mice, and DM mice treated with 5% AST-120. Six weeks after hind-limb ischemia surgery, blood flow reperfusion, histology, plasma AGE, and cytokine were examined. Bone marrow cells were cultured and derived into macrophages to evaluate the effects of AGEs on macrophage polarization. Results Plasma AGEs were significantly increased in diabetic mice. AST-120 could bind to AGEs and reduced their plasma concentrations. Histological analysis revealed fewer collateral vessels with corresponding impairment of blood flow recovery in diabetic mice. In these mice, AGE-positive and AGE receptor-positive macrophages were numerous in ischemic limbs compared with non- diabetic mice. In diabetic mice, macrophages in ischemic tissues demonstrated greater M1 polarization than M2 polarization; this pattern was reversed in the AST-120 treatment group. The change in macrophage polarization was associated with the corresponding expression of pro-inflammatory cytokines in the ischemic tissues. In cell cultures, AGEs triggered the transformation of bone marrow-derived macrophages into the M1 phenotype. The alterations in the polarization of macrophages were reversed after treatment with AST-120. Conclusions Oral administration of AST-120 decreased the serum levels of AGEs in diabetic mice and improved neovascularization of ischemic limbs. This benefit may be due to, at least partially, the alterations in macrophage polarization and the associated changes in inflammatory cytokines. Graphical abstract: Proposed mechanism of AGE effects on post-ischemia neovascularization and tissue remodeling through the modulation of macrophage phenotype in diabetes. Unlabelled Image Highlights: Oral AST-120 reduced the plasma levels of AGEs. AST-120 improved neovascularization and blood flow recovery in ischemic diabetic mice. Polarity of macrophages in ischemic diabetic mice was pro-inflammatory M1 phenotype. AST-120 therapy reversed this polarity into the pro-angiogenic M2 phenotype.